Model for personnel allocation and selection of off-duty groups in a textile company - Kramer, Hugo Harry F. R.; Subramanian, Anand; DAngelis, Luiz Guilherme Binder; Pires, Carlos Eduardo G. L. (Revista Gestão da Produção Operações e Sistemas, 2008)
This paper deals with the resolution of the personnel assignment problem and the selection of the off-workgroups of employees belonging to a certain sector of a major textile industry. This is a problem of great importancefor most organizations, since it is fundamental to assign the set of available workers, with distinct levels ofskill and qualification, to the best suitable tasks. Hence, a multidimensional assignment model was built, takinginto account the operational and functional particularities of the sector, as well as considering the benefit of assigningsome worker to a determined section of the same. The optimum solution obtained maximized the globalbenefit of the assignments and at the same time allowed the identification of the off-work groups of employeesin the sector studied.Keywords: Multidimensional assignment problem; Off-work groups; Benefit.